2023
DOI: 10.1021/acsanm.2c05272
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Polymer–Lipid Hybrid Nanoparticles to Enhance In Vivo Exposure and Uptake of Repaglinide in Brain Cells to Treat Diabetes-Linked Neurodegenerative Disorders

Abstract: Repaglinide (REP), an antidiabetic drug, is recently explored in ameliorating neurodegenerative disorders (Huntington's and Alzheimer's disease) by targeting neuronal calcium sensors (DREAM/ATF6 pathway). The repurposing of REP faces odds due to its short half-life and poor brain permeability. To circumvent these, we have developed and evaluated PEGylated nanocarriers, i.e., polymer−lipid hybrid nanoparticles (PLHNPs), for oral delivery of REP in the treatment of diabetes mellitus (DM)-linked neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…This study demonstrated that this hybrid nanoparticle increased the targeting ability of Riv to the brain, but therapeutic efficacy should be investigated in future studies. Wadhwa et al administered pegylated polymer–lipid hybrid nanoparticles via oral delivery to treat diabetes-linked neurodegenerative diseases, and results showed that the mice treated with nanoparticles had improved retention memory . This study provided a comprehensive investigation in vitro and in vivo , including drug design, drug release, therapeutic efficacy, and biodistribution analysis, which indicated a promising strategy to enhance drug delivery for diabetes-linked neurodegenerative diseases.…”
Section: Nanotechnology-based Strategies For Brain Drug Deliverymentioning
confidence: 80%
“…This study demonstrated that this hybrid nanoparticle increased the targeting ability of Riv to the brain, but therapeutic efficacy should be investigated in future studies. Wadhwa et al administered pegylated polymer–lipid hybrid nanoparticles via oral delivery to treat diabetes-linked neurodegenerative diseases, and results showed that the mice treated with nanoparticles had improved retention memory . This study provided a comprehensive investigation in vitro and in vivo , including drug design, drug release, therapeutic efficacy, and biodistribution analysis, which indicated a promising strategy to enhance drug delivery for diabetes-linked neurodegenerative diseases.…”
Section: Nanotechnology-based Strategies For Brain Drug Deliverymentioning
confidence: 80%
“…The lipid layer can consist of lecithin or cholesterol and an additional lipid, e.g., DSPE (1,2-distearoyl-sn-glycero-3-phosphoethanolamine) or DOPE (1,2-dioleoyl-sn-glycero-3-phosphoethanol-amine), which are conjugated with polyethylene glycol (PEG). The function of the lipid layer is to ensure biocompatibility and stability, while the functional PEGylated lipids additionally improve the water solubility of the particles, reducing the aggregation tendency through steric stabilization [ 11 , 13 , 15 ]. The PEG shell serves as a stealth coating that prevents opsonization, resulting in a prolonged circulation time of DDS in the bloodstream [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%